The Effect Of Land Cover Changes On Landslides In Grindulu Watershed, Pacitan Regency, East Java - Fauzi, Raka Achmad (EDP Sciences, 2023)
This research was conducted in the Grindulu River Watershed, Pacitan Regency. The Grindulu River is included in the Bengawan Solo river area. The Grindulu River Watershed is located in three areas, namely Pacitan Regency, Ponorogo Regency and Community Dis tricts along the River Watershed use the grindulu river water for various activities, such as bathing, washing, and for agricultural irrigation purposes. This study aims to determine changes in land cover in the Grindulu river watershed and the distribution of landslides in the Gindulu river area. The data used in this study is information consisting of: data on landslide events in 2022 obtained from the Pacitan Regency regional disaster management agency; land cover data for the grindulu river watershed in 2018 and 2022 identified from Copernicus Sentinel-2; basic maps, such as road network maps, contour maps, river network maps and administrative maps obtained from the Indonesian Land map.Based from the spatial analysis, it was found that 67 points of landslide events that occurred during 2022 were spread throughout the river watershed. The landslide occurrence points have patterns or clusters located on the banks of the river and close to residential areas. Landslide points are found in different land covers based on spatial analysis of the distribution of landslide points with land cover maps. Most landslides occur in agroforestry land cover. © The Authors, published by EDP Sciences. All Rights Reserved.